2016
DOI: 10.2147/lctt.s60344
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 as a novel molecular target in non-small-cell lung cancer

Abstract: Lung cancer remains the most lethal cancer, with over 160,000 annual deaths in the USA alone. Over the past decade, the discovery of driver mutations has changed the landscape for the treatment of non-small-cell lung cancer (NSCLC). Targeted therapies against epidermal growth factor receptor (EGFR) or anaplastic lymphoma kinase (ALK) have now been approved by the Food and Drug Administration as part of the standard first-line treatment of NSCLC. Despite good initial responses, most patients develop resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Previous studies have shown that Akt1 interacts with the heat shock protein 90 (Hsp90) ( Sato et al, 2000 ; Esfahani and Cohen, 2016 ; Giulino-Roth et al, 2017 ). Interestingly, Hsp90 is a binding partner of HAX-1 ( Lam et al, 2013 , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Akt1 interacts with the heat shock protein 90 (Hsp90) ( Sato et al, 2000 ; Esfahani and Cohen, 2016 ; Giulino-Roth et al, 2017 ). Interestingly, Hsp90 is a binding partner of HAX-1 ( Lam et al, 2013 , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, HAX-1 was reported to interact with Hsp90 ( Lam et al, 2013 , 2015 ), a chaperone protein. Hsp90 assists other proteins to fold properly and can stabilize a number of proteins involved in tumor growth, which makes Hsp90 an investigatory target in cancer research ( Esfahani and Cohen, 2016 ). In particular, HAX-1 has been reported in recent years to combine with Hsp90 to adjust the expression of Cyclophilin-D and IRE-1, which can separately regulate the mitochondrial apoptosis and ER stress-related apoptosis ( Lam et al, 2013 , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to of their strong dependence on HSP90, inhibition of the latter leads to ubiquitin-mediated proteasomal degradation of client proteins concluding with the downregulation of different oncogenic signalling pathways [19]. Since EGFR [20], BRAF [21], ERBB2 [22], MET [23,24] and the EML4-ALK translocation product [8] are clients of HSP90, acting as oncodrivers in different clinico-pathological subsets of lung adenocarcinoma, degradation of these oncoproteins through HSP90 inhibition leads to loss of tumor-cell viability [25,26,27,28]. Promising results have been shown in different clinical studies, especially in malignancies that possess an HSP90 client as an oncodriver [29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of the globular domain in EML4-ALK results in a relatively unstable fusion protein which recruits HSP90 [137]. Therefore, EML4-ALK variant 1 is sensitive to HSP90 inhibitor treatment and clinical trials in NSCLC patients using these inhibitors have shown promising results [142].…”
Section: Other Alk Fusion Proteins Are Causative Of Cancermentioning
confidence: 99%